Investigation on Pressure Relief and Roadway Protection Technology by Subsection Hydraulic Fracturing under Strong Mining Pressure in Fully Mechanized Mining. (11th August 2022) - Liu, Yingjie
Abstract : In this study, we analyzed the deformation and stress changes of an auxiliary transport gateway in Buertai coal mine 42106, which is a fully mechanized coal face. We used the directional long drilling hydraulic fracturing technology to weaken the mine hard roof clearance and investigated the overall pressure characteristics of the working face, mining, and two consecutive roadway surrounding rock deformations. The analysis showed that the segmented hydraulic fracturing technology of directional long drilling decreased the pressure in the area affected by the fracturing drilling on the working face after fracturing. The peak pressure decreased by approximately 10.4%, average resistance of the stent was reduced by 2.6%, average resistance of the support decreased by 6.8% under pressure, and dynamic load coefficient decreased by 4%. Furthermore, the roadway deformation decreased, and the coal face was restrained. The stress monitoring value of the surrounding rock was weakened, demonstrating the effectiveness of the fracturing weakening effect.